An efficient strategy for full mineralization of an azo dye in wastewater: a synergistic combination of solar thermo- and electrochemistry plus photocatalysis. Issue 58 (20th July 2017) - Nie, Chunhong; Dong, Jing; Sun, Pingping; Yan, Chao; Wu, Hongjun; Wang, Baohui
Abstract : An efficient strategy for full mineralization of azo dye in wastewater. Abstract : Herein, a synergistic combination of three flows, i.e. photo-flow, thermo-flow, and electro-flow, from solar energy was first constructed and then utilized for the mineralization of an azo dye in wastewater. Taking methyl orange as an example, the mineralization of the azo dye was theoretically and experimentally investigated. The results indicated that the oxidation efficiency of the photo-electro-thermo flows could reach up to 81.88% within 60 min, which was superior to those of the corresponding single flow or two flows, and full mineralization to CO2 was realized. The mechanism of mineralization was discussed by comparing the molecular conjugate chain detected by UV and the intermediate products identified by HPLC and GC. Non-linear regression was used to obtain the rate equation of methyl orange mineralization. A significant synergetic effect of solar thermo- and electrochemistry plus photocatalysis was observed. The evidence shows that the synergistic application of three flows from solar energy can greatly provide an effective way for the enhancement of the utilization of solar energy and the oxidation of azo dye pollutants.